An overview of behavioral economics in Dutch policy making. the next step: how to nudge policy makers - Els Stroeker, Natasha (Applied Studies in Agribusiness and Commerce, 2016)
This article describes the beginning of the influence of behavioral economics on the Dutch government. This started in the period that the UK started with its Behavioral Insights Team (BIT UK). The article presents explanation of the concept “nudging” and the way this is integrated in Dutch policy. Also leading publications and examples of how behavioral economics is used in policy making are presented. The advice of the government in 2014 on how to ensure a structural integration of behavioral science knowledge in policy is part of the next step. The next step contains two main parts: 1. How to nudge policy makers and 2. Embedding nudges in policy making on four aspects: positioning, projects, performance and professionality.